Human Resource Development within European Social Fund in Poland - Tracz‑Krupa, Katarzyna (Edukacja Ekonomistów i Menedżerów, 2014)
The purpose of this article is to demonstrate and illustrate the results of spending meas‑ ures in Poland of European Social Fund (ESF), which supports human resource develop‑ ment and, in particular, the systematic improvement of employee qualification. A start‑ ing point is the presentation of the European Social Fund in Poland. Then the Human Resource Development (HRD) is defined and analyzed from a few theoretical perspectives. In the following part of the article an analysis of progress is made in implementation of the strategic objectives of the Human Capital Operational Program (HCOP) and then the results of the implementation of the European Social Fund in Poland are presented. The final section shows conclusions and future research directions.